2019
DOI: 10.1007/s11357-019-00055-5
|View full text |Cite
|
Sign up to set email alerts
|

High rates of undiagnosed vascular cognitive impairment among American Indian veterans

Abstract: As data on prevalence and etiology of dementia in American Indians are limited, we sought to determine rates and patterns of memory loss among American Indian veterans with vascular risk factors. Sixty consecutive outpatient American Indian veterans with a mean age of 64 years (range 50-86), without prior dementia or mild cognitive impairment (MCI), and with ≥ 2 vascular risk factors were enrolled. The Montreal Cognitive Assessment (MoCA) and the Beck Depression Inventory-II were used to screen for cognitive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…An additional 10 studies identified employment of Indigenous staff or community members for data collection, field work or trial coordination (Garvey et al, 2011; Jacklin, Pitawanakwat, Blind, Lemieux, et al, 2020; Jervis & Manson, 2007; Korn et al, 2009; Lo Giudice et al, 2016; Smith et al, 2007; Smith et al, 2008; Smith et al, 2009; Smith et al, 2010; Verney et al, 2008) and one study reported using a cultural advisor (White et al, 2019). No information about Indigenous leadership or involvement were reported for 33 studies (Blix & Hamran, 2017; Carty et al, 2020; Chen et al, 2019; Cotter et al, 2012; Cullum et al, 2018; Cullum et al, 2020; Derrig et al, 2020; Fife et al, 2020; Hanssen, 2013; Jacklin et al, 2013; Jernigan et al, 2020; Jervis et al, 2007; Kirkpatrick et al, 2019; Lewis et al, 2020; Li et al, 2014; Mayeda et al, 2017; Mayeda et al, 2016; Mehta et al, 2008; Panegyres et al, 2021; Petrasek MacDonald et al, 2015; Pu’un et al, 2014; S. Russell et al, 2021; Russell et al, 2016; Sentell et al, 2015; Smith et al, 2021; Wadsworth et al, 2016; Waller et al, 2021; Weiner et al, 2007; Weiner et al, 2003; Weiner et al, 2008; Weiner et al, 2011; Whyte et al, 2005; Wiese et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional 10 studies identified employment of Indigenous staff or community members for data collection, field work or trial coordination (Garvey et al, 2011; Jacklin, Pitawanakwat, Blind, Lemieux, et al, 2020; Jervis & Manson, 2007; Korn et al, 2009; Lo Giudice et al, 2016; Smith et al, 2007; Smith et al, 2008; Smith et al, 2009; Smith et al, 2010; Verney et al, 2008) and one study reported using a cultural advisor (White et al, 2019). No information about Indigenous leadership or involvement were reported for 33 studies (Blix & Hamran, 2017; Carty et al, 2020; Chen et al, 2019; Cotter et al, 2012; Cullum et al, 2018; Cullum et al, 2020; Derrig et al, 2020; Fife et al, 2020; Hanssen, 2013; Jacklin et al, 2013; Jernigan et al, 2020; Jervis et al, 2007; Kirkpatrick et al, 2019; Lewis et al, 2020; Li et al, 2014; Mayeda et al, 2017; Mayeda et al, 2016; Mehta et al, 2008; Panegyres et al, 2021; Petrasek MacDonald et al, 2015; Pu’un et al, 2014; S. Russell et al, 2021; Russell et al, 2016; Sentell et al, 2015; Smith et al, 2021; Wadsworth et al, 2016; Waller et al, 2021; Weiner et al, 2007; Weiner et al, 2003; Weiner et al, 2008; Weiner et al, 2011; Whyte et al, 2005; Wiese et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Studies were mostly conducted in Australia with Aboriginal and/or Torres Strait Islander people (n = 30, see Figure 3) (Arkles et al, 2020; Bryant et al, 2021; Cotter et al, 2012; Cox et al, 2019; Derrig et al, 2020; Dingwall et al, 2017; Garvey et al, 2011; Hocking et al, 2019; Lavrencic et al, 2019; Li et al, 2014; Lindeman et al, 2012; Lo Giudice et al, 2016; Lo Giudice et al, 2011; LoGiudice et al, 2006; Panegyres et al, 2021; Radford et al, 2019; Radford, Mack, Draper, Chalkley, Daylight, et al, 2015; Radford, Mack, Draper, Chalkley, Delbaere, et al, 2015; S. Russell et al, 2021; Russell et al, 2016; S. G. Russell et al, 2021; Smith et al, 2016; Smith et al, 2010; Smith et al, 2009; Smith et al, 2008; Smith et al, 2011; Smith et al, 2007; Taylor et al, 2012; Waller et al, 2021; White et al, 2019). Twenty-three studies were conducted in the United States of America with Native American Indian, Alaskan and Hawaiian people (Browne et al, 2021; Carty et al, 2020; Fife et al, 2020; Jernigan et al, 2020; Jervis et al, 2007; Jervis & Manson, 2007; Kirkpatrick et al, 2019; Korn et al, 2009; Lewis et al, 2020; Martindale-Adams et al, 2017; Mayeda et al, 2016, 2017; Mehta et al, 2008; Sentell et al, 2015; Smith et al, 2021; Verney et al, 2008; Wadsworth et al, 2016;…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, our findings suggest that even in adults with generally low levels of activity, modest increases in mid-life PA are associated with higher cognitive test scores in later life. This finding is particularly relevant for AI adults, who may have higher burdens of risk factors for cognitive impairment and be more likely to suffer from cognitive impairment than other race/ethnicity groups [28, 29]. These data combined with the projected growth of the elder population from 7.4% of the AI population in 2010 to 16.8% in 2050 [2] highlight the urgent need for interventions focused on cognitive impairment risk reduction in this at-risk population.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding VCID in all populations will have significant impact considering that some bear a greater burden of or are at greater risk of cognitive impairment (e.g., Black/African Americans, American Indian/Alaska Natives, Latinx compared to Asian Americans or non‐Hispanic White Americans 83 , 84 ), some have more vascular risk factors and comorbidities (e.g., Latinx, Black/African Americans, American Indians 84 , 85 , 86 ), some have unique exposures or differing social and structural circumstances that increase risk or impact care (e.g., sex‐specific exposures such as preeclampsia and menopause; 87 , 88 discrimination and racism; 84 social stigma, and fewer potential caregivers among sexual and gender minorities 89 ). Studying diverse groups can also give unique insights into protective factors.…”
Section: Perspectives and Priorities For Future Researchmentioning
confidence: 99%